Citral Induced Apoptosis through Modulation of Key Genes Involved in Fatty Acid Biosynthesis in Human Prostate Cancer Cells: In Silico and In Vitro Study. (18th March 2020) - Balusamy, Sri Renukadevi; Perumalsamy, Haribalan; Veerappan, Karpagam; Huq, Md. Amdadul; Rajeshkumar, S.; Lakshmi, T.; Kim, Yeon Ju
Abstract : The isomers of citral ( cis -citral and trans -citral) were isolated from the Cymbopogon citratus (DC.) Stapf oil demonstrates many therapeutic properties including anticancer properties. However, the effects of citral on suppressing human prostate cancer and its underlying molecular mechanism have yet to be elucidated. The citral was isolated from lemongrass oil using various spectroscopic analyses, such as electron ionized mass spectrometry (EI-MS) and nuclear magnetic resonance (NMR) spectroscopy respectively. We carried out 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay to evaluate the cell viability of citral in prostate cancer cells (PC-3 and PC3M). Furthermore, to confirm that PC3 undergoes apoptosis by inhibiting lipogenesis, we used several detection methods including flow cytometry, DNA fragmentation, Hoechst staining, PI staining, oil staining, qPCR, and Western blotting. Citral impaired the clonogenic property of the cancer cells and altered the morphology of cancer cells. Molecular interaction studies and the PASS biological program predicted that citral isomers tend to interact with proteins involved in lipogenesis and the apoptosis pathway. Furthermore, citral suppressed lipogenesis of prostate cancer cells through the activation of AMPK phosphorylation and downregulation of fatty acid synthase (FASN), acetyl coA carboxylase (ACC), 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGR), and sterol regulatory element-binding protein (SREBP1) and apoptosis of PC3 cells by upregulating BAX and downregulating Bcl-2 expression. In addition, i n silico studies such as ADMET predicted that citral can be used as a safe potent drug for the treatment of prostate cancer. Our results indicate that citral may serve as a potential candidate against human prostate cancer and warrants in vivo studies.